Spin-Iattice coefficients of Mn2+ in II-VI compounds. - Causa, M. T.; Tovar, M.; Oseroff, S. B.; Calvo, R.; Giriat, W. (North Holland Publishing Co., 1980)
Fil: Causa, M. T. Comisión Nacional de Energía Atómica; Argentina